Hybrid systems biology : 5th International Workshop, HSB 2016, Grenoble, France, October 20-21, 2016, proceedings /: 5th International Workshop, HSB 2016, Grenoble, France, October 20-21, 2016, proceedings. (2016) - Unknown
No abstract available